Liberalism Revisited: The Most Relevant Political Theory for Today's Global Challenges - Tirkey, C. Anupa (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
Liberalism has evolved over centuries to become the cornerstone of modern political and economic systems. Rooted in Enlightenment principles, liberalism promotes individual rights, democracy, and free markets as essential components of a just society. Despite its evolution, liberalism has remained central to contemporary political discourse, offering solutions to global challenges such as human rights violations, authoritarianism, and economic inequality. This paper examines the evolution of liberalism, its key principles, its contemporary relevance, and the criticisms it faces in the present age, arguing that liberalism remains the most adaptable and relevant political theory in today's world.